Effect of Tremella fuciformis polysaccharide on the stalling and flavor of tteok during storage - Hongxiu Fan; Hongcheng Liu; Wenyi Li; Wenjing Su; Dawei Wang; Shanshan Zhang; Tingting Liu; Yanrong Zhang (Food Science and Human Wellness)
The effect of Tremella fuciformis polysaccharide (TFP) on the retrogradation property and aroma profile changes of tteok during storage was investigated. Results indicated that addition of TFP significantly increased the stability to thermal and mechanical shearing of starch, decreased short-term retrogradation, the hardness and the retrogradation enthalpy (ΔH) of tteok during storage, but had no significant effect on the amylopectin chain length of tteok. The possible mechanism for the retarding staling effect of TFP is related to the interaction between TFP and starch chains that interferes with the alignment of starch chains. Electronic nose and gas chromatography-mass spectrum (GC-MS) analysis results showed that the difference in the concentrations of volatile compounds and fatty acids of tteoks at different storage time gradually increased with the advancement of storage period. The addition of TFP to tteok inhibited the development of unpleasant volatile compounds, probably by delaying the oxidation and decomposition of lipids and preserving the antioxidant phenolic compounds in tteok, thus slowing down the flavor deterioration of tteok and contributing to flavor maintainace. Overall, this study could help food manufacturers to choose a high-effective and natural polysaccharide to control the retrogradation rate and flavor loss of tteok.